Mejoramiento de la calidad de vida de la población escolar de los niños de segundo, tercero, cuarto y quinto año de la escuela “Ramón Burneo” del barrio Zalapa bajo de la parroquia el Valle, cantón Loja, provincia de Loja; mediante la atención básica bucodental considerando su perfil epidemiológico periodo marzo – septiembre del 2010 - León Aguilar, Yadira Elizabeth (2010)
This research work aims to: know the most prevalent and make the lifting of the epidemiological profile of oral diseases in children in second, third, fourth and fifth years of the School "Ramon Burneo" Loja City to improve the quality of life of the school. For this study, 33 children diagnosed in this school, who underwent the respective treatments and after it was analyzed the results, which indicate the DMFT values: 1.57 (low risk) in children in the fourth year and 4.08 (High Risk) in fifth-grade girls. Children 10 years have a value of 3 (moderate risk) and girls an index of 3.16 (moderate risk). Besides was made the dmft index, with a value of 8.85 (high risk) in children in third year and a 10.35 (High Risk) in girls. At the age of 6 years, children had a value of 10 (High Risk) and girls of 9 years a rate of 8.83 (High Risk), showing a deft high rate of girls. To determine the incidence of caries in boys and in girls, was conducted a clinical assessment in which 88.23% was found in children and 100% in girls. Poor oral hygiene leads to the accumulation of bacterial plaque, food remains and calculus, this are predisposing factors in the development of periodontal diseases such as gingivitis. In this study, were found values of 100% of plaque and food remains in boys, while girls have ratios of 93.75%. As for oral rehabilitation in children performed the following activities: 253 operative dental, 105 sealants, 55 extractions, 4 pulp treatments, and 33 prophylaxis with fluoride application. Keywords: dmft index, DMFT index, dental caries, gingivitis